2013
DOI: 10.19026/ajas.5.4842
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Effect of Climate Change on Food Security of Rural Households in Cross River State, Nigeria

Abstract: The study focused on the linkage between climate change and food security of rural households in Cross River state. The specific objectives are to ascertain the level of food security of rural households and impacts of climate change factors on the food security of rural households. Cross River State is located within Latitude 05°13' 26'' North and longitude 08° 17' 44'' East with an estimated population of 2.888,966 persons. The state is a coastal area usually affected by climate events (flooding) coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…129 Several studies have shown that social, economic and environmental factors affect food security. Socio-economic factors such as income, household size, credit access, livestock ownership, level of education, farm size, sex, age of head of household, marital status (Ahmed and Dotti, 2014;Djangmah, 2016;Goshu, 2016;Ajaero, 2017;Dawit and Zeray, 2017) and environmental factors such as climate change, soil fertility, drought and flooding (Nzeadibe et al, 2011;Emaziye et al, 2013;Yaro, 2013) all define level of food security. Flooding as an environmental factor affecting food security has not been extensively studied in South-eastern Nigeria, even though Ramakrishna et al (2014) and Zakari et al (2014) found flooding to have negative impacts on food security in India and Niger Republic, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…129 Several studies have shown that social, economic and environmental factors affect food security. Socio-economic factors such as income, household size, credit access, livestock ownership, level of education, farm size, sex, age of head of household, marital status (Ahmed and Dotti, 2014;Djangmah, 2016;Goshu, 2016;Ajaero, 2017;Dawit and Zeray, 2017) and environmental factors such as climate change, soil fertility, drought and flooding (Nzeadibe et al, 2011;Emaziye et al, 2013;Yaro, 2013) all define level of food security. Flooding as an environmental factor affecting food security has not been extensively studied in South-eastern Nigeria, even though Ramakrishna et al (2014) and Zakari et al (2014) found flooding to have negative impacts on food security in India and Niger Republic, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, an analysis of climate change events (rainfall variability), food insecurity and human mobility in three villages located in the same district of Kilimanjaro found a positive correlation between rainfall shortage and out-migration and identified food insecurity as mediator in that relationship [ 119 ]. In Nigeria, a 2013 analysis of climate change events including temperature and rainfall from January 1971 to December 2009 in the Cross River State, prone to floods and oil spill hazards, found that climate change events were associated with rural household food insecurity, contributing to an estimated annual agricultural productivity loss of 67.7% [ 120 ].…”
Section: Climate Change Burden To Public Healthmentioning
confidence: 99%
“…Niger Delta is a diverse and dense region in southern Nigeria that includes nine states with over 30 million people, including Akwa Ibom where our project site is located (Ike & Emaziye, 2012). While the Niger Delta region is known for its rich natural and ecological resources, its residents suffer from inadequate access to healthcare, limited access to primary healthcare, and insufficient policy/financial/infrastructure support (Omuta, 2015).…”
Section: Introductionmentioning
confidence: 99%